The Role of Resilience and Social Support in Predicting Postdeployment Adjustment in Otherwise Healthy Navy Personnel. Issue 9 (1st September 2014) - Cunningham, Craig A.; Weber, Bryan A.; Roberts, Beverly L.; Hejmanowski, Tracy S.; Griffin, Wayne D.; Lutz, Barbara J.
ABSTRACT: The purpose of this study was to determine if resilience, social support, and exposure to combat, stressful deployment environments, and additional stressful life events predicted short-term (12 months or less) postdeployment adjustment in a relatively healthy subset of Navy service members. One hundred and thirty-two service members between 3 and 6 months postdeployment completed anonymous surveys at a deployment health center. Service members with probable post-traumatic stress disorder and those who were at risk for harm to self or others were excluded. There was relatively low variance in exposure to combat, stressful deployment environments, and additional stressful life events for this convenience sample. Although the sample was a relatively healthy subset of service members and conclusions may not be generalizable to larger populations, 56% endorsed considerable adjustment difficulties. Results of logistic regression indicated that greater resilience, greater postdeployment social support, and less stressful deployment environments predicted greater postdeployment adjustment. Resilience and postdeployment social support remained significant predictors of postdeployment adjustment when controlling for covariates. Results also suggest that individual augmentee experience may be a protective factor against postdeployment adjustment difficulties—at least in otherwise healthy service members.